2003
DOI: 10.1034/j.1399-6576.2003.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

International publishing in anaesthesia – how do different countries contribute?

Abstract: The geographic distribution of the publications on anaesthesiology must not only be analysed in absolute numbers, where the USA is the most productive. The North-European countries show the largest production/number of inhabitants ratio; whereas the largest percentage increase during the period is found in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 16 publications
6
32
0
Order By: Relevance
“…Potential causes, notably inadequate funding, have been raised in . Similar concerns have been expressed regarding a decline in randomised controlled trials from Canadian departments [4] and in contributions to anaesthesia journals from departments in the United States [3,10,11] and these results are also consistent with our data. These authors have suggested shortages of anaesthesia providers, lack of research time for anaesthetists and a lack of formalised research programs for trainees in anaesthesia as contributory factors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Potential causes, notably inadequate funding, have been raised in . Similar concerns have been expressed regarding a decline in randomised controlled trials from Canadian departments [4] and in contributions to anaesthesia journals from departments in the United States [3,10,11] and these results are also consistent with our data. These authors have suggested shortages of anaesthesia providers, lack of research time for anaesthetists and a lack of formalised research programs for trainees in anaesthesia as contributory factors.…”
Section: Discussionsupporting
confidence: 82%
“…1), notably that we hand-searched [5,6] each article to determine its categorisation as an original article, editorial etc., rather than rely on the classification provided by MEDLINE [10]. While our methodology is more conservative, it will perhaps allow more robust comparisons to be made in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recently research has been done in the fields of anesthesiology [1], cardiology [2], and medical informatics [3]. Other geographic analyses have compared biomedical publications in the European Union and in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Previous geographic studies of countries' contribution to research on other diseases have consistently shown that the U.S. share of scientific literature relative to other countries has declined over the last two decades (Figueredo, Sanchez, & Munoz, 2003;Kessler et al, 1995;Nahrwold, Pereira, & Dupuis, 1995;Rahman & Fukui, 2002). The main objectives of the present study are (a) to map changes in national contributions to PTSD research over the last two decades as an indicator of the diagnosis' international acceptance, (b) to assess whether the share of research from countries other than the United States has increased in PTSD as it has in other areas, and (c) to compare the quality of the research conducted in each country using scientific articles' number of citations as an indicator of excellence.…”
mentioning
confidence: 98%